Strategic Approaches to Sustainable Lithium Extraction: Advances in Technology, Resource Recovery, and Environmental Management - Neha Sahu; Rizwan Arif (International Journal of Minerals, 2024)
Lithium, a critical mineral for modern technological advancements, is in high demand due to its role in the production of lithium-ion batteries, which power electric vehicles, portable electronics, and renewable energy storage solutions. This paper provides a comprehensive overview of lithium’s sources, including pegmatites, brine deposits, and sedimentary lithium minerals, while examining production, extraction methodologies, and challenges related to sustainability and environmental impact. Additionally, advancements in laser-induced breakdown spectroscopy (LIBS) for lithium mapping and quantification are discussed, alongside innovations aimed at optimizing resource recovery and recycling. Future demand forecasts emphasize the critical role of lithium in supporting the global shift toward low-carbon energy technologies, while highlighting risks and strategies for mitigating socio-ecological impacts, especially in regions with significant lithium reserves. The paper concludes by addressing the need for sustainable mining practices, improvements in extraction technology, and a more circular approach to lithium use.
Keywords: Environmental impact; Rechargeable Batteries; lithium extraction; lithium-ion technology; resource recovery; sustainable mining